Quadruple Helix As A Business Communication Model Of Jakarta MSME Assistance - Tursanurohmad, Noviana; Nimran, Umar; Raharjo, Kusdi; Nayati Utami, Hamidah (Publisher Cv. Inara, 2023)
The objective of this study is to examine the implementation of the quadruple helix business communication strategy for digitizing MSMEs in Jakarta. Specifically, the study aims to assess the effectiveness of the strategy in increasing awareness and understanding of digitalization among MSME players and to evaluate its impact on the development of digital skills and capabilities. This study adopts a qualitative research method. The qualitative component involves conducting interviews with key stakeholders, including government officials, academics, business representatives, and MSME players. These interviews aim to gather insights into their perceptions and experiences regarding the quadruple helix strategy and its implementation in MSME digitalization efforts. The quadruple helix business communication strategy is a collaborative approach involving government, academics, business people, and society to achieve common goals. This strategy is particularly relevant in the context of digitizing micro, small, and medium enterprises (MSMEs) in Jakarta, as it can enhance awareness and understanding among MSME players regarding the importance of digitalization. Additionally, this strategy can help MSME players develop their digital skills and capabilities. The implementation of the quadruple helix business communication strategy in Jakarta's MSME digitalization efforts is coordinated by HIPMIKINDO, which serves as a communication hub connecting the government, academics, and MSME players. Rather than acting as an initiator, HIPMIKINDO positions itself as a collaborator among the four main stakeholders, forming a quadruple helix framework for effective communication.